1989
DOI: 10.1161/01.cir.79.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate adjustment of ST segment depression for improved detection of coronary artery disease.

Abstract: Normal values for heart rate-adjusted indexes of ST segment depression during treadmill exercise electrocardiography (the ST segment/heart rate slope and the AST segment/heart rate index) were derived from evaluation of 150 subjects with a low likelihood of coronary artery disease, including 100 normal subjects and 50 subjects with nonanginal chest pain. Partitions chosen by the method of percentile estimation to include 95% of normal subjects remained highly specific in subjects with nonanginal pain syndromes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
4

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(86 citation statements)
references
References 33 publications
4
78
0
4
Order By: Relevance
“…Because both the AST/HR index and ST/HR slope are continuous variables that reflect this relation in a quantitative fashion, their values can be accurately related to both the presence and severity of CHD. 3,12,13,25,29 In contrast, during early recovery, the magnitude of ST segment depression in patients with CHD generally remains greater than expected for the rapidly decreasing myocardial oxygen demand that results from an abrupt lowering of exercise load, producing a counterclockwise rate-recovery loop pattern.14 Because direction of the rate-recovery loop is not dependent on a particular threshold magnitude of ST segment depression at peak exercise, sensitivity of this method for identifying CHD may be less affected by the anatomic and functional severity of underlying coronary obstruction than are standard and heart rate-adjusted criteria that are derived from exercise-phase data alone.14 Although the AST/HR index significantly concentrates risk in the present study, the more complex ST/HR slope method might have performed with greater accuracy. Although the ST/HR slope relates changing ST depression to heart rate changes occurring during maximum ischemia, the AST/HR index relates overall ST depression to the total heart rate change during exercise.12,'325,29 Because this total change in heart rate may include a variable period of effort during which ischemia is absent, the AST/HR index should not as effectively normalize ST depression for oxygen demand during ischemia as does the maximal ST/HR slope and, therefore, may not as accurately reflect the presence and severity of coronary obstruction.29 Further study is necessary to evaluate the potential of this method to stratify risk of coronary events; this may be facilitated by the recent implementation of accurate, on-line computerized calculation of the ST/HR slope.50…”
Section: Study Populationmentioning
confidence: 99%
“…Because both the AST/HR index and ST/HR slope are continuous variables that reflect this relation in a quantitative fashion, their values can be accurately related to both the presence and severity of CHD. 3,12,13,25,29 In contrast, during early recovery, the magnitude of ST segment depression in patients with CHD generally remains greater than expected for the rapidly decreasing myocardial oxygen demand that results from an abrupt lowering of exercise load, producing a counterclockwise rate-recovery loop pattern.14 Because direction of the rate-recovery loop is not dependent on a particular threshold magnitude of ST segment depression at peak exercise, sensitivity of this method for identifying CHD may be less affected by the anatomic and functional severity of underlying coronary obstruction than are standard and heart rate-adjusted criteria that are derived from exercise-phase data alone.14 Although the AST/HR index significantly concentrates risk in the present study, the more complex ST/HR slope method might have performed with greater accuracy. Although the ST/HR slope relates changing ST depression to heart rate changes occurring during maximum ischemia, the AST/HR index relates overall ST depression to the total heart rate change during exercise.12,'325,29 Because this total change in heart rate may include a variable period of effort during which ischemia is absent, the AST/HR index should not as effectively normalize ST depression for oxygen demand during ischemia as does the maximal ST/HR slope and, therefore, may not as accurately reflect the presence and severity of coronary obstruction.29 Further study is necessary to evaluate the potential of this method to stratify risk of coronary events; this may be facilitated by the recent implementation of accurate, on-line computerized calculation of the ST/HR slope.50…”
Section: Study Populationmentioning
confidence: 99%
“…We have found that bias resulting from this factor can significantly affect the reputed accuracy of exercise testing. 15 An example of such bias is illustrated in the report of Kligfield et al 5 These investigators excluded equivocals (17% of study group) from the numerators for the calculation of sensitivity and specificity. In an overview of 147 publications, we found this treatment of equivocal results used only one time.22 Such a biased treatment of equivocals falsely improves both sensitivity and specificity.23 The test results so assigned and therefore excluded involved upsloping ST segments.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the accuracy of the exercise ECG, various indices have been proposed, including the degree of STsegment depression, 1,16,17 R wave amplitude changes, 18,19 ST/HR slope, 20,21 ST index, 21,22 QT dispersion, 2,23 ST slope 1,7,16,24,25 and concomitant changes in hemodynamic parameters. 1,17 Each has been reported to improve accuracy; however, only a few are in clinical use, presumably because there has not been a dramatic increase in accuracy, the method is complicated or time-consuming, or both.…”
Section: Diagnostic Value Of St Slopementioning
confidence: 99%